COMMUNICATION OF THE CENTRAL BANK AS A DETERMINANT OF THE CREDIBILITY AND EFFECTIVENESS OF THE MONETARY POLICY ON THE EXAMPLE OF THE EUROPEAN CENTRAL BANK - Piotr Misztal (Polityki Europejskie, Finanse i Marketing, 2023)
The aim of the undertaken research is an attempt to explain, on theoretical and empirical grounds, the interdependence between central bank communication, its transparency credibility and,consequently, the effectiveness of monetary policy pursued by central banks. The study used research methods based on the literature analysis on the subject in the field of banking and finance, as well as statistical and econometric methods (Granger causality analysis and the generalised linear model – GLM). Literature studies are aimed at answering the question of what is the relationship between the transparency, credibility of the central bank and the effectiveness of monetary policy in theoretical terms. However, the empirical research studies aim to confirm the hypothesis (H0) or reject the hypothesis (H1) about the causal relationships between the variables mentioned. Empirical analyses were conducted on the example of the European Central Bank, which, from the point of view of its monetary policy, is characterised by relatively high efficiency, relatively effectively stabilising inflation in the monetary union. All statistics used in the study were taken from databases of the International Monetary Fund (IMF World Economic Outlook), the European Union statistical office (Eurostat) and the Organisation for Economic Cooperation and Development (OECD) (OECD Data). The analysis covers the period from 2010 to 2022 based on monthly data. The results of the research confirmed the existence of the null hypothesis (i.e., the significant impact of communication, transparency and credibility of the European Central Bank on the effectiveness of monetary policy in the Euro area). The results of the conducted research may be a starting point for further, more in-depth research on the relationship between communication, transparency, credibility and effectiveness of central banks in countries with different levels of economic development.